Qualitative and Quantitative Hippocampal MRI Assessments in Intractable Epilepsy. (28th July 2013) - Singh, Paramdeep; Kaur, Rupinderjeet; Saggar, Kavita; Singh, Gagandeep; Kaur, Amarpreet
Abstract : Aims. To acquire normative data of hippocampal volumes and T2 relaxation times, to evaluate and compare qualitative and quantitative assessments in evaluating hippocampi in patients with different durations of intractable epilepsy, and to propose an imaging protocol based on performance of these techniques. Methods. MRI analysis was done in 50 nonepileptic controls and 30 patients with intractable epilepsy on 1.5T scanner. Visual assessment and hippocampal volumetry were done on oblique coronal IR/T2W and T1W MP-RAGE images, respectively. T2 relaxation times were measured using 16-echo Carr-Purcell-Meiboom-Gill sequence. Volumetric data was normalized for variation in head size between individuals. Patients were divided into temporal (n = 20 ) and extratemporal (n = 10 ) groups based on clinical and EEG localization. Results. In controls, right hippocampal volume was slightly more than the left with no effect of age or gender. In TLE patients, hippocampal volumetry provided maximum concordance with EEG. Visual assessment of unilateral pathology concurred well with measured quantitative values but poorly in cases with bilateral pathologies. There were no significant differences of mean values between extratemporal group and controls group. Quantitative techniques detected mild abnormalities, undetected on visual assessment. Conclusions. Quantitative techniques are more sensitive to diagnose bilateral and mild unilateral hippocampal abnormalities.